Pembuatan Peta Indikatif Berbasis SIG untuk Mendukung Pengembangan Potensi Lokal Desa Uko: Pengabdian - La’bi, Zet Linda Allo; Dendi; Alim, Bimanatara Nur (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The objective of this program is to produce an indicative map of Uko Village, Muara Komam Subdistrict, Paser Regency, which can be used to develop local potensial. Uko Village has vast natural resources and a large area, but there is no spatial visualization that can show the overall condition of the area. This makes it difficult for village officials to formulate data-based policies, especially those related to spatial planning and land use. The method used is the utilization of Geographic Information Systems (GIS) through three main stages, namely field surveys, data preparation, and data processing. The field survey was conducted by collecting coordinate points using GPS and digital map applications, which were then combined with village administrative data from Ina Geoportal and ArcGIS satellite imagery. The spatial data was processed using ArcGIS software with UTM Zone 50S, WGS 1984 projection, and produced a 1:80,000 scale map. The result of this activity is an indicative map of Uko Village containing information on administrative boundaries, residential areas, road networks, river flows, public facilities, and land use in the form of coffee plantations (±0.09 ha), rubber plantations (±0.04 ha), and oil palm plantations (±0.04 ha). This map provides a comprehensive overview of the existing conditions of the village and can be used as an analytical tool for spatial planning, identification of local economic potential, infrastructure development, and environmental management. Thus, the indicative map serves as a strategic document in supporting the targeted, effective, and sustainable development of Uko Village.